Analisis Investasi Proyek IT dalam Bina Nusantara - Suryawan, Angellia Debora (Bina Nusantara University, 2013)
Companies should be able to adapt to the rapid development of IT. Therefore, IT is a must requirement for companies that want competent in today's business competition. The company must prepare budget that does not cheap for IT investment in order to meet global market competition. Companies need to really check and make sure that their IT investments will indeed be useful and profitable, or can obtain return of investment (ROI) at least. Companies also need to choose the right investments and in accordance with the company's business needs, so that IT can assist in improving corporate profits. This study aims to analyze utility of IT investment, IT investments in the budgeting process, and how the processes and methods of measurement and calculation of a good budgeting. Therefore, companies may prevent any losses on the IT investment. It is expected that through this study companies can decide whether the IT investment is feasible or not feasible to be implemented. Besides, companies can measure whether the investment will it be beneficial or detrimental.